2020
DOI: 10.1538/expanim.19-0079
|View full text |Cite
|
Sign up to set email alerts
|

Hemogram study of an artificially feeding tree shrew (<i>Tupaia belangeri chinensis</i>)

Abstract: Systematic classification and determination of various cells in normal peripheral blood of artificially feeding Tupaia belangeri chinensis of different ages and genders and evaluation of the effectiveness of an automatic blood cell classification counter for measuring tree shrew blood cells. Child, young and adult tree shrews (forty for each group) were randomly selected, half male and half female. After the animals were stable, the peripheral blood of each group was collected through the femoral vein, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The qualitative and semiquantitative urinalysis revealed leucocytes and elevated levels of urobilinogen, ketones, bilirubin, protein, and glucose. Compared with available reference values for Tupaia spp., 10,11,15,22,34,38,41,42 the hematological and biochemical profiles had low concentrations of alkaline phosphatase, aspartate aminotransferase, and creatine kinase; elevated creatinine, chloride, and glucose; and reduced albumin and total protein levels. The calcium-to-phosphorus ratio was 2.1:2.7 (Supplemental Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The qualitative and semiquantitative urinalysis revealed leucocytes and elevated levels of urobilinogen, ketones, bilirubin, protein, and glucose. Compared with available reference values for Tupaia spp., 10,11,15,22,34,38,41,42 the hematological and biochemical profiles had low concentrations of alkaline phosphatase, aspartate aminotransferase, and creatine kinase; elevated creatinine, chloride, and glucose; and reduced albumin and total protein levels. The calcium-to-phosphorus ratio was 2.1:2.7 (Supplemental Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The values for leukocytes (2.21 × 10 9 /L) and neutrophils (0.85 × 10 9 /L) are below the lower limit of the human reference value. The lymphocytes, eosinophils, basophils and monocytes of tree shrews are generally within the reference range for humans ( 36 – 38 ). Biochemical analysis showed that only the creatinine results for tree shrews are below the lower limit of the human reference value, while the alanine aminotransferase and aspartate transaminase values are above the upper limit of the reference value.…”
Section: Tree Shrew Physiology and Biochemistrymentioning
confidence: 99%
“…Immunological processes of tree shrews correlate strongly with the disease progression (Parkin & Cohen, 2001). The immune system of tree shrews is similar to that of humans, including the similar neutrophil percentage and similar morphology and size of erythrocytes (Feng et al, 2020). Zhang et al found, for the first time in 2020, that the serum of tree shrews immunized with polysaccharides could induce antibody‐dependent bactericides, suggesting that the immune response of humans is more like that of tree shrews than of rodents (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%